SOFTWARE MANAGEMENT OF GTAW WELDING PARAMETERS WITH AN 8-AXIS ADAPTIVE ROBOTIC SYSTEM BY ANALYZING THE RESULTS OBTAINED ON SAMPLES AND TEST PIECES (Nonconventional Technologies Review, 2020)
The objective of the article is to briefly detail the main aspects that can influence the accuracy, reliability, flexibility and productivity of a robotic welding system. The article describes the welding process used by the robotic system to obtain experimental data. The welding parameters that have been managed in the software program of the robotic system are presented in order to obtain satisfactory samples and test pieces. The experimental part followed the study of samples and test pieces obtained after managing the welding parameters by their software implementation. For the selected experimentation scenario, the article establishes the values of the welding parameters implemented in the software program of the robotic system.
Keywords: robotic system; welding parameters; software program; samples; test pieces; management